Approach of immersive adaptive learning for Virtual Reality simulator - Vega, Alieski Véliz; Madrigal, Omar Correa; Kugurakova, Vlada (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and Education, 2021)
The need to improve teaching-learning processes promotes the development of Virtual Reality applications with adaptive learning approaches. Adaptive learning considers the premise that each person learns differently, at their own pace, considering the characteristics of the student. This paper describes the main components of an immersive adaptive learning approach for Virtual Reality simulators.